Effects of NatureKnit™ organic, a blend of organic fruit and vegetable fibers rich in naturally occurring bound polyphenols, on the metabolic activity and community composition of the human gut microbiome using the M-SHIME® gastrointestinal model - Govaert, Marlies; Duysburgh, Cindy; Kesler, Brendan; Marzorati, Massimo (Frontiers in Nutrition, 2026)
ObjectivesThe effects of a proprietary blend of organic fruit and vegetable fibers rich in naturally occurring bound polyphenols (commercially known as NatureKnit™ Organic) on the human gut microbiome were assessed.MethodsShort-term (48 h) in vitro colonic simulations using the validated Mucosal Simulator of the Human Intestinal Microbial Ecosystem (M-SHIME®) platform, with fecal inoculum from nine individual healthy human donors, were performed. Purified organic fibers (inulin and psyllium) were evaluated as comparators and a negative control was included. Primary measures included pH, gas pressure, short-chain fatty acid (SCFA) production, and microbial community composition.ResultsAll test products were well fermented with NatureKnit™ Organic showing slower fermentation kinetics than the purified fibers. SCFAs were significantly increased with all test products versus the negative control (p < 0.0001 for all) and NatureKnit™ Organic reached significance versus both purified fibers (p < 0.0001 for both). While relative abundances in the mucosal compartment were similar among all test conditions, luminal bacterial abundance increased with NatureKnit™ Organic and psyllium versus the negative control. The latter was mainly associated with statistically increased abundance (p < 0.05) of the genera Eisenbergiella and Monoglobus, with an additional strong enrichment of Bacteroidaceae. Furthermore, bacterial species richness was significantly increased with NatureKnit™ Organic versus the negative control (p = 0.0495), which was not observed for the purified organic fibers (p = 0.0567 and p = 0.4285 for inulin and psyllium, respectively).ConclusionOverall, the obtained results indicate that NatureKnit™ Organic may have a greater and gentler prebiotic effect compared with established purified prebiotic fibers.